RNF43 is a tumour suppressor gene mutated in mucinous tumours of the ovary. Issue 3 (25th January 2013) - Ryland, Georgina L; Hunter, Sally M; Doyle, Maria A; Rowley, Simone M; Christie, Michael; Allan, Prue E; Bowtell, David DL; ,; Gorringe, Kylie L; Campbell, Ian G
Abstract Mucinous carcinomas represent a distinct morphological subtype which can arise from several organ sites, including the ovary, and their genetic characteristics are largely under‐described. Exome sequencing of 12 primary mucinous ovarian tumours identified RNF43 as the most frequently somatically mutated novel gene, secondary to KRAS and mutated at a frequency equal to that of TP53 and BRAF. Further screening of RNF43 in a larger cohort of ovarian tumours identified additional mutations, with a total frequency of 2/22 (9%) in mucinous ovarian borderline tumours and 6/29 (21%) in mucinous ovarian carcinomas. Seven mutations were predicted to truncate the protein and one missense mutation was predicted to be deleterious by in silico analysis. Six tumours had allelic imbalance at the RNF43 locus, with loss of the wild‐type allele. The mutation spectrum strongly suggests that RNF43 is an important tumour suppressor gene in mucinous ovarian tumours, similar to its reported role in mucinous pancreatic precancerous cysts. Copyright © 2012 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.